Analisis rasio keuangan terhadap return saham perbankan yang terdaftar di bursa efek Indonesia: Periode 2015–2024 - Erna Garnia; Rikah Yuliana Febriani; Siti Riyyan Lisaumi; Fitria Lilyana (Jurnal STEI Ekonomi, 2026)
Banking stock returns in Indonesia exhibit significant fluctuations driven by various company fundamental factors. This study aims to analyze the effect of Debt to Asset Ratio (DAR), Net Profit Margin (NPM), and Return on Investment (ROI) on the stock returns of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2015–2024 period. The research employs a quantitative approach using panel data regression analysis on 15 sample companies selected through purposive sampling, resulting in 150 observations. The results indicate that partially, DAR has a significant negative effect on stock returns, whereas NPM and ROI do not show significant effects. These findings suggest that capital structure is the primary risk consideration for investors in banking stock investment decisions, while operational profitability and investment efficiency have not yet become decisive signals during the observation period.